2010
DOI: 10.4317/medoral.15.e709
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical comparative study of the odontogenic keratocysts and other odontogenic lesions

Abstract: Objectives: The present study was undertaken to compare the pattern of expression of EGFR, cyclin D1, Ki-67, p-53 and carcinoembryonic antigen (CEA) in the epithelial lining of odontogenic keratocysts, dentigerous cysts, radicular cysts and ameloblastomas. Methods: four micrometers, formalin-fixed, paraffin-embedded tissue sections from 11 odontogenic keratocysts, 10 dentigerous cysts, 10 radicular cysts and 10 ameloblastomas were immunohistochemically studied. Results: There were statistically significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 21 publications
6
32
1
5
Order By: Relevance
“…That could probably be related with the biological aggressiveness of AB and OKCs. Results of AB and OKC's relation differs from what Juan-Carlos de-Vicente et al (12) found. This difference is likely to be explained by differences in staining process.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…That could probably be related with the biological aggressiveness of AB and OKCs. Results of AB and OKC's relation differs from what Juan-Carlos de-Vicente et al (12) found. This difference is likely to be explained by differences in staining process.…”
Section: Discussioncontrasting
confidence: 54%
“…The overexpression of this protein shows accelerated G1 progression entering in the S-phase of cell cycle, with lower cell dependence on growth factors for proliferation. Cyclin D1 may play an important role in tumorigenesis and it has been detected in malignant tumors but also in benign neoplasms (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, when IPO-38 was used as a proliferation marker, it was found that the labeling index of IPO-38 was higher in ameloblastomas than in dentigerous cysts (49). However, another study conducted by de Vicente et al demonstrated that Ki-67 expression was higher in dentigerous cysts than in ameloblastomas (50). Furthermore, dentigerous cyst have been found to have significantly higher counts for the proliferative activity marker nucleolar organizer regions than unicystic ameloblastoma (51).…”
Section: A B C D E F G Hmentioning
confidence: 94%
“…Partial maxillectomy or mandibulectomy is the most common treatment choice with safety margin of healthy bone to avoid recurrence (6). World Health Organization (WHO) working group recommends the term of keratocystic odontogenic tumor which stresses the neoplastic nature of the entity instead of odontogenic keratocyst for parakeratinized variants (5,7,8). A more "innocent" entity ortokeratinized odontogenic keratocyst (OKK) is not included in this novel classification, is still classified in developmental odontogenic cysts (5,9).…”
Section: Introductionmentioning
confidence: 99%